The ethical action in the professional exercise of the accountant and the application of corporate social reponsability - Piedra Luna, Jorge Humberto (2019)
Successive business scandals have revealed that the professional training of accountants is not enough since current trends in the accounting profession are entangled in innumerable cases of fraud and corruption, not only in Ecuador, but throughout the Latin American region. This affects the users of financial information, understood as investors, control bodies, and the state itself, which are interested in the reasonableness of the financial statements for proper decision making. Professional ethics is a necessity that has prevailed over time, becoming a transversal axis for each individual formed with values and principles since their action affects society. For this reason, the objective of this work is to determine the ethical performance in the professional practice of the accountant and the application of corporate social responsibility, through epistemological review for a new insight of the profession. The methodology applied to achieve the objective was the bibliographic review of the epistemological approach that the accountant has determined as a complete professional, who puts the interests of the company before their own, in addition, the agreement according to the objectives undertaken by the company and society.